2021
DOI: 10.11646/zootaxa.4908.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Description and bioecology of two new species of the genus Cryncus (Orthoptera, Gryllidae, Gryllinae) from Cameroon with a key and distribution map of all African species 

Abstract: The genus Cryncus Gorochov, 1983 composed of African crickets is reported for the first time in Cameroon by the description of two new species collected at Zamakoe, Ongot and Engout’Adjap in the southern Cameroonian plateau during an inventory study of crickets carried out from March 2014 to September 2015. These new species are: Cryncus camerounensis Um Nyobe, Kekeunou & Bilong Bilong sp. nov. and Cryncus desutterae Um Nyobe, Kekeunou & Ma sp. nov. These descriptions bring the total number of species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 826 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The characteristics of each study locality and a map can be found in the publication of Um Nyobe et al (2021). In these habitats, crickets were captured from March 2014 to September 2015 using pitfalls and quadrats, according to the methodology described in Um Nyobe et al (2021). The methodology used for the identification based on internal and external morphology is the one presented in the publication of Um Nyobe et al (2022).…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of each study locality and a map can be found in the publication of Um Nyobe et al (2021). In these habitats, crickets were captured from March 2014 to September 2015 using pitfalls and quadrats, according to the methodology described in Um Nyobe et al (2021). The methodology used for the identification based on internal and external morphology is the one presented in the publication of Um Nyobe et al (2022).…”
Section: Methodsmentioning
confidence: 99%